2021
DOI: 10.1002/tox.23108
|View full text |Cite
|
Sign up to set email alerts
|

SMAR1 attenuates the stemness of osteosarcoma cells via through suppressing ABCG2 transcriptional activity

Abstract: The promoting roles of the transcriptional regulator SMAR1 have been revealed in several tumors, such as colorectal and breast cancer, however, its roles in osteosarcoma (OS) progression are still confusing. Here, we find that SMAR1 expression is positively correlated with the overall survival of OS patients and negatively correlated with the expression of stemness markers by analyzing the online datasets. Through analyzing different Gene Expression Omnibus (GEO) datasets, SMAR1 is found to be lowly expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…It has been shown that the number of tumorigenic stem cells is directly proportional to the progression of cancers, these cells being involved in the initiation of tumorigenesis, tumor angiogenesis, metastases, drug resistance and recurrences. Stem cells are characterized by increased drug and chemotherapeutic resistance due to their expression in the efflux pump of ABCG2 [ 160 ]. It is located on the interface of the blood-brain barrier (efflux capacity of the protein protects the central nervous system from compounds with endogenous toxicity), placenta, liver, kidneys, colon and small intestine [ 161 , 162 , 163 , 164 , 165 , 166 , 167 ].…”
Section: Flavonoidsmentioning
confidence: 99%
“…It has been shown that the number of tumorigenic stem cells is directly proportional to the progression of cancers, these cells being involved in the initiation of tumorigenesis, tumor angiogenesis, metastases, drug resistance and recurrences. Stem cells are characterized by increased drug and chemotherapeutic resistance due to their expression in the efflux pump of ABCG2 [ 160 ]. It is located on the interface of the blood-brain barrier (efflux capacity of the protein protects the central nervous system from compounds with endogenous toxicity), placenta, liver, kidneys, colon and small intestine [ 161 , 162 , 163 , 164 , 165 , 166 , 167 ].…”
Section: Flavonoidsmentioning
confidence: 99%
“…In 3D cultures of ABCB1-high/ABCA1-low chemo-immune-resistant cells, expression of the doxorubicin effluxer ABCB1 was upregulated by the Ras/ERK1/2/HIF-1α signaling axis, which suggests the existence of pathway crosstalk to reinforce an already chemoresistant phenotype in osteosarcoma cells [ 93 ]. ABCG2 transcriptional activity was also suppressed by the transcriptional regulator SMAR1, which increased the ABCG2 deacetylation level via HDAC2 and also decreased the ALDH activity [ 94 ]. miRNA-221 also seems to increase P-glycoprotein expression via the Stat3 pathway and promoting doxorubicin-resistance [ 95 ].…”
Section: Mechanisms Of Csc Resistance To Conventional Therapiesmentioning
confidence: 99%
“…miR‐26a directly binds to the 3′‐noncoding region of JAGGED1, a ligand of NOTCH, and inhibits the translation or degradation of JAGGED1 messenger RNA and downstream JAGGED1/NOTCH signaling (J. Lu et al, 2017). In addition, there are many genes that can affect the proliferation and growth of osteosarcoma cells by changing the stemness of OSCs (Basu‐Roy et al, 2015; Y. Chen et al, 2020; Liang et al, 2019; W. Liu et al, 2018; B. Lu et al, 2020; M. L. Tang et al, 2018; J. Wang et al, 2021; H. Y. Xu et al, 2017; H. Xu et al, 2021; Z. Yu et al, 2018; Zhao et al, 2017).…”
Section: Genes Related To Oscsmentioning
confidence: 99%